A mensa ponderaria in the Casa dell’Atrio Tetrastilo from Nora (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2020)
The essay overviews the morphological and metrological profile of an umpublished mensa ponderaria reused in one of Casa dell’Atrio Tetrastilo’s stonework, in Nora. Such object it’s the only one hailed from Sardinia and it probably founds its originating position in a horreum-insula along the road towards the harbour, otherwise in the commercial building depending on the domus itself.
Keywords: Casa dell’Atrio Tetrastilo; mensa ponderaria; Nora; Sardinia